2008
DOI: 10.1051/0004-6361:20078596
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical period changes in HT Cassiopeiae: a difference between systems above and below the period gap

Abstract: Aims. We report identification of cyclical changes in the orbital period of the eclipsing cataclysmic variable HT Cas. Methods. We measured new white-dwarf mid-eclipse timings and combined them with published measurements to construct an observed-minus-calculated diagram covering 29 years of observations. Results. The data present a 36 yr period modulation of semi-amplitude ∼40 s, with a statistical significance greater than 99.9 percent with respect to a constant period. Conclusions. We combine our results wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 78 publications
(92 reference statements)
2
38
0
Order By: Relevance
“…As for many other CVs, HT Cas is a short period binary system (P orb 1.77 h, Borges et al 2008), close to the lower edge of the period gap at ∼2.5 h. The system is characterized by a visual magnitude of ∼16.4 during its quiescent state, relatively rare outbursts (Horne et al 1991), and white dwarf eclipses well observed in several optical campaigns. A detailed analysis of the light curves can be found in Patterson (1981) and Wood et al (1985).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…As for many other CVs, HT Cas is a short period binary system (P orb 1.77 h, Borges et al 2008), close to the lower edge of the period gap at ∼2.5 h. The system is characterized by a visual magnitude of ∼16.4 during its quiescent state, relatively rare outbursts (Horne et al 1991), and white dwarf eclipses well observed in several optical campaigns. A detailed analysis of the light curves can be found in Patterson (1981) and Wood et al (1985).…”
Section: Introductionmentioning
confidence: 69%
“…There has also been a report of a cyclical change in the HT Cas orbital period (ΔP/P ∼ 4 × 10 −7 , see Borges et al 2008, for details). The authors attributed this effect to a loss of angular momentum caused by the coupling of the stellar wind from the companion star to the surface of the compact object.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the contrary, they appear rather to be the rule. Borges et al (2008) compiled a list of 14 systems exhibiting this phenomenon which contains most of the brighter eclipsing CVs, well observed over a long time base. An updated version was published by Pilarčík et al (2012), who also included some post-common envelope binaries (PCEBs) with similar period variations.…”
Section: The Cyclic Period Variationsmentioning
confidence: 99%
“…The same phenomenon is observed in semi-detached binaries, such as Algols and cataclysmic variables. The latter are particularly interesting because they show the phenomenon also when their secondary components are fully convective (Ak et al 2001;Borges et al 2008), thus providing a circumstantial evidence of magnetic cycles in fully convective dwarf stars with a sufficiently fast rotation. For more information on the connection between orbital period modulation and dynamo action see, e.g., Lanza et al (1998), Lanza & Rodonò (1999), Lanza & Rodonò (2004), Lanza (2005), and Lanza (2006a).…”
Section: Stellar Cycles From Photospheric Proxiesmentioning
confidence: 99%